Circulating Current Suppression Control Method for Distributed Grid-Connected Converter - HU Liang; ZHOU Zhenbang; MEI Wenqing; WANG Yue; FU Jianguo; LIU Yayun (Kongzhi Yu Xinxi Jishu)
Distributed three-level converters operate in a grid-connected state through an input-parallel output-parallel (IPOP) mode. These converters offer advantages such as high efficiency, high flexibility, and low cost, making them widely applicable in new energy scenarios such as energy storage converter and photovoltaic converter. Grid-connected converters are deemed one of important solutions in the context of increasing proportions of renewable energy utilization and power electronic equipment application. In order to suppress circulating currents in distributed IPOP three-level grid-connected converter systems, this paper proposes a circulating current suppression control method specific for this type of converters. A power equivalent model was established to simulate zero-sequence circulating currents, allowing for the analysis of harmonic components in circulating currents based on the carrier disposition modulation of injected zero-sequence voltage. The proportional complex integral (PCI) method is introduced for compensating for the zero-sequence modulation of each independent controller, to suppress low-frequency circulating currents between converters. Moreover, zero-sequence DC component suppression is integrated in the virtual speed governor link to achieve comprehensive control. The method proposed eliminated over 90% of the circulating current components in simulations and experiments, verifying the correctness and effectiveness of the zero-sequence circulating current modeling and suppression approach.